Sistem Informasi Penjualan Pada Toko Rial-Harmonika Berbasis Website - Fahlevi, Reza (mijournal.org, 2024)
Rial-Harmonika is a business entity focused on the sale, production, and installation of harmonica screens. However, this company faces challenges in managing orders and customer service, such as manual transaction recording systems that increase the risk of data loss. To address these issues, the author proposes implementing information technology titled